Electronic Logbook sebagai Strategi Quality Improvement Model Preceptorship dan Mentorship Perawat - Anggita Dian Puspita; Enie Novieastari; Hanny Handiyani; Sri Herni Wigiarti (Journal of Telenursing (JOTING), 2023)
This study aims to identify problems and develop a quality improvement strategy design in the perinatology installation of X Hospital. The method used is a case report using an action research approach. The results showed that the majority level of the preceptor's role was still low (68.2%), but the psychological empowerment and self-efficacy level of preceptor nurses was high (54.5%; 59.1%). The story of commitment to the preceptor's role and the preceptor's perception of benefits and rewards was also low (66.7%; 66.7%), but the preceptor's perception of support was high (66.7%). Evaluation of the implementation of the electronic logbook obtained data that the majority of nurses felt that the role and function of the head of the room in program implementation were good and the technical evaluation of program implementation was also appropriate, but the need for socialization in implementing the program needed to be increased again. In conclusion, nurse managers must strive to educate and improve the motivation and commitment of nurses in supporting the change program, followed by program monitoring and evaluation activities. Keywords: Electronic Logbook, Mentorship, Nurse, Preceptorship